KELUARGA SEBAGAI BASIS KERUKUNAN UMAT BERAGAMA DI SEI GOHONG, PALANGKA RAYA KALIMANTAN TENGAH - Dudi, Josef; Bramantyo, Rizki Yudha (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
Abstract The process of carrying out worship is a personal matter, as a social being, of course it cannot be separated from social interaction. This condition continues to occur in Sei Gohong, Central Kalimantan. Therefore, the discussion of the personality or social profile of the Sei Gohong community is a meaning framework in guiding a comprehensive analysis. Understanding social profiles is very important in order to give weight to the analysis of the social interactions of the religious plural community in Sei Gohong. Understanding of the social profile begins with the family profile. Because it is reflected in the personality and character of each family member, which ultimately leads to the community. This study uses a qualitative descriptive approach, with purposive techniques as an approach to determine informants, and observation, interview and documentation techniques as data collection techniques. The source data validation test is used to test the correctness of the data. Interactive analysis techniques are used to analyze data. The results showed that the family is the basic social institution that has the most role in determining the patterns of interaction of a community group. The family form in Sei Gohong is generally the nuclear family and is a family that is tied to the family, which has a strong influence on social mechanisms and interaction processes. Therefore, family ties are an important element in overcoming differences, including differences in their religion. There is an epistemic sensitivity in interfaith marriages. Keywords: Family; Bahadat and Pahuni; Plural ReligiousAbstrak Proses menjalankan ibadah merupakan urusan pribadi, sebagai makhluk sosial tentu tidak lepas dari interaksi sosial. Kondisi inilah yang terus terjadi di Sei Gohong Kalimantan Tengah tersebut. Oleh karena itu pembahasan kepribadian atau profil sosial masyarakat Sei Gohong merupakan kerangka makna dalam menuntun analisis yang menyeluruh. Pemahaman profil sosial menjadi sangat penting guna memberikan bobot analisis terhadap interaksi sosial masyarakat plural agama di Sei Gohong. Pemahaman profil sosial tersebut diawali dari profil keluarga. Sebab tercermin kepribadian dan karakter dari setiap penghuni keluarga, yang akhirnya bermuara pada masyarakat. Penelitian ini menggunakan pendekatan deskriptif kualitatif, dengan teknik purposive sebagai pendekatan untuk menentukan informan, dan teknik observasi, wawancara serta dokumentasi sebagai teknik pengumpulan data. Uji validasi data sumber digunakan untuk menguji kebenaran data. Teknik analisis interaktif digunakan untuk menganalisis data. Hasil penelitian adalah keluarga merupakan institusi sosial dasar yang paling berperan dalam mentukan  pola interaksi suatu kelompok masyarakat. Bentuk keluarga di Sei Gohong umumnya keluarga inti dan merupakan keluarga yang terikat dengan keluarga, yang mempunyai pengaruh kuat dalam mekanisme sosial dan proses interaksi. Oleh karena itu, ikatan keluarga menjadi unsur penting dalam mengatasi perbedaan-perbedaan, termasuk perbedaan agama yang mereka anut. Terdapat kepekaan epistemik dalam perkawinan beda agama. Kata Kunci: Keluarga; Bahadat dan Pahuni; Plural Agama